2012
DOI: 10.15560/8.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians and reptiles, Romblon Island group, central Philippines: comprehensive herpetofaunal inventory

Abstract: We present results from several recent herpetological surveys in the Romblon Island Group (RIG), Romblon Province, central Philippines. Together with a summary of historical museum records, our data document the occurrence of 55 species of amphibians and reptiles in this small island group. Until the present effort, and despite past studies, herpetological diversity of the RIG and their biogeographical affinities has remained poorly understood. We report on observations of evolutionarily distinct amphibian spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 47 publications
7
43
0
Order By: Relevance
“…Important habitats we observed that are critical to species survival include riparian vegetation, leaf litter, tree stumps, dead logs, fallen trees, tree foliage, swamps, and creeks, all of which are found in forested areas. Our observations are consistent with those from other studies Brown et al 2001Brown et al , 2012Brown et al , 2013bMcleod et al 2011;Siler et al 2011Siler et al , 2012Gaulke 2011;Devan-Song & Brown 2012;Plaza & Sanguila 2015;Siler et al 2016), emphasizing how these habitats are among the highest priority for research and conservation value.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Important habitats we observed that are critical to species survival include riparian vegetation, leaf litter, tree stumps, dead logs, fallen trees, tree foliage, swamps, and creeks, all of which are found in forested areas. Our observations are consistent with those from other studies Brown et al 2001Brown et al , 2012Brown et al , 2013bMcleod et al 2011;Siler et al 2011Siler et al , 2012Gaulke 2011;Devan-Song & Brown 2012;Plaza & Sanguila 2015;Siler et al 2016), emphasizing how these habitats are among the highest priority for research and conservation value.…”
Section: Discussionsupporting
confidence: 93%
“…In recent work of Siler et al (2011) in Aurora Province, the authors demonstrated that a single survey is not sufficient to assess the species diversity of an area Siler et al, 2011). In these and several other studies, authors nearly doubled species diversity for a given site with subsequent survey efforts (Brown et al , 2013bSiler et al 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They are commonly observed within rotting logs, in leaf litter, in the root networks of tree buttresses, as well as beneath rotting piles of coconuts (Siler et al 2012b). The species has been found to qualify for a conservation status of “Near Threatened” (NT; IUCN 2016; Siler et al 2012a,b). …”
Section: Species Accountsmentioning
confidence: 99%
“…These efforts have focused on the northern Babuyan and Batanes islands (Oliveros et al 2011), the large northern island of Luzon (McLeod et al 2011; Siler et al 2011a; Brown et al 1996, 2000a, 2012a, 2013a; Devan-Song and Brown 2012), and central island groups (Brown and Alcala 1961, 1964, 1986; Siler et al 2012a), but little recent activity has documented other parts of the archipelago, especially the western island of Palawan, the Sulu Archipelago, and portions of the large southern island of Mindanao (Leviton 1963; Brown and Alcala 1970a; Peterson et al 2008; Jones and Kennedy 2008; Siler et al 2009). Mindanao supports high levels of herpetological diversity (Taylor 1920a,b, 1921, 1922a,b; Brown and Alcala 1970; Brown et al 2013a; Diesmos et al 2015) and considerable endemism, despite its close proximity to the larger landmasses of Sundaland (Borneo, Sumatra, and Java) and Wallacea (Sulawesi; Fig.…”
Section: Introductionmentioning
confidence: 99%